Chikungunya Virus Infection of Cell Lines: Analysis of the East, Central and South African Lineage - Wikan, Nitwara; Sakoonwatanyoo, Prirayapak; Ubol, Sukathida; Yoksan, Sutee; Smith, Duncan R. (PLOS ONE, 2012)
Chikungunya virus (CHIKV) is a re-emerging mosquito borne alphavirus that has caused large scale epidemics in the countries around the Indian Ocean, as well as leading to autochthonous transmission in some European countries. The transmission of the disease has been driven by the emergence of an African lineage of CHIKV with enhanced transmission and dissemination in Aedes mosquito hosts. Two main genotypes of this lineage have been circulating, characterized by the presence of a substitution of a valine for an alanine at position 226 of the E1 protein. The outbreak, numbering in millions of cases in the infected areas, has been associated with increasing numbers of cases with non-classical presentation including encephalitis and meningitis. This study sought to compare the original Ross strain with two isolates from the recent outbreak of chikungunya fever in respect of infectivity and the induction of apoptosis in eight mammalian cell lines and two insect cell lines, in addition to generating a comprehensive virus production profile for one of the newer isolates. Results showed that in mammalian cells there were few differences in either tropism or pathogenicity as assessed by induction of apoptosis with the exception of Hela cells were the recent valine isolate showed less infectivity. The Aedes albopictus C6/36 cell line was however significantly more permissive for both of the more recent isolates than the Ross strain. The results suggest that the increased infectivity seen in insect cells derives from an evolution of the CHIKV genome not solely associated with the E1:226 substitution.